Relative Energy Deficiency in Sport (RED-S) - a consequence of the pursuit of perfection - a literature review - Bździuch, Patrycja; Cencelewicz, Katarzyna; Miciuda, Paulina; Buziak, Jakub; Grzywacz-Guza, Aleksandra; Hatala, Patrycja (Quality in Sport, 2026)
Introduction and purpose: Relative Energy Deficiency in Sport (RED-S) is a multifactorial syndrome that negatively affects a wide range of physiological and psychological functions in athletes. It is often linked to high training loads, inadequate nutrition, and pressures related to performance and body composition. The pursuit of perfection in sport can encourage behaviors such as excessive training and restrictive eating, which increase the risk of developing RED-S. The purpose of this review is to summarize current knowledge on the causes, risks, and consequences of RED-S in athletes. It also aims to provide guidance for effective prevention and management strategies. State of knowledge: RED-S arises when athletes’ energy intake does not meet the demands of training and basic bodily functions, leading to disruptions in endocrine, metabolic, bone, and immune health, as well as mental well-being. It can affect both male and female athletes across a variety of sports, not only those emphasizing leanness. The condition can impair performance, slow recovery, and increase the risk of injuries. Growing awareness of RED-S has led to improvements in screening, diagnosis, and management practices within sports and clinical settings. Conclusions: Despite being motivated by high performance aspirations, striving for an ideal body composition or optimal performance can increase the risk of developing RED-S, which may lead to serious health consequences. Increasing awareness can help promote preventive measures and improve health among the athlete population.